Bulk chemical composition of manganese nodules at various levels of their external manganese rich layers - Tsunogai, Shizuo; Nakanishi, Keita; Yamada, Masatoshi (PANGAEA, 2023)
The nodules used in this study were collected from two cruises in the western North Pacific by box coring (KH-79-4) and dredging (GH-78-1). After being dried at 110°C each sample extracted from the top, side and bottom of the nodule at various penetration levels, a chemical separation technique was used in a 6% acetic acid solution (fraction A). The residual was then submitted to a mixture 6% (IM) acetic acid and IM hydroxylamine hydrochloride (a reducing agent). The leachant is designated as fraction B and the dry residual (fraction B). On each part, acetylene-air flame atomic absorption spectrophotometry was used for the determination of Fe, Mn, Co and Ni. Aluminium was determined by acetylene-nitrous oxide flame atomic absorption spectrophotometry. Flameless atomic absorption spectrophotometry was used to determine Co, Ni and Cu. Dissolved silicate was determined by the standard colorimetric method of molybdenum yellow by adding boric acid as a masking agent for fluoride. The table presents the bulk composition as a recombination of the 3 parts analysed.
Keywords: Geochemistry; growth; manganese micronodule; manganese nodule; ocean; sediment